Mannette: I'm Coming Back Home - Nero, Sean (Newsday)
Elliot "Ellie" Mannette states that he will be returning to Trinidad after 30 years abroad. He hopes to return to Trinidad and Tobago and bring his team of pan technicians to the Unvieristy of the West Indies and share his knowledge.
Keywords: Steel drum (Musical instrument) -- Trinidad and Tobago; Mannette, Ellie; Arrangers (Musicians) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago